ANTIMICROBIAL PROPERTIES OF NANO-EMULSION FORMULATED FROM GARLIC, GINGER AND CINNAMON EXTRACTS AGAINST Escherichia coli AND Salmonella typhi - Hernani Hernani; Kun Tanti Dewandari (Indonesian Agency for Agricultural Research and Development, 2018)
Garlic, ginger and cinnamon had been reported for their antimicrobial activities, for instance against Escherichia coli and Salmonella typhi. The present study aimed to test antimicrobial activities of nanoemulsion of the mixture of garlic, ginger and cinnamon. The nanoemulsion was formulated from the mixture of garlic and ginger extracts and cinnamon essential oil at the ratio of 80:10:10 using a high pressure homogenizer at 300 bars for 5 cycles. The nanoemulsion powder was prepared using a spray dryer with the inlet and outlet temperatures of 160–170 °C and 70–80 °C, respectively, and maltodextrin as a filler. The nanoemulsion was tested against E. coli and S. typhi. The particle size of nanoemulsion and powdered formulas were characterized using a scanning electron microscope. The LC50 values were identified based on the Brine Shrimp Lethality Test. The results showed that quality of the raw materials confirmed the WHO requirements. The particle size of the emulsion ranged from 151 to 306 nm with the polydispersity index of 0.39–0.52. The 10% and 15% active compounds of the nanoemulsion inhibited E. coli and S. thypi with the LC50 values of 680.15–970.50 ppm and 607.17–903.31 ppm, respectively. The study suggests that the nanoemulsion of a mixture of garlic, ginger and cinnamon extracts could be developed as a food preservative.